The Influence of The Independent Curriculum and Field Work Practice on Students' Competency Mastery in Vocational High Schools - Yunadi Al Gifari Paputungan; Stella Junus; Monica Pratiwi; Buyung R. Machmoed; Sugeng Pramudibyo (Faculty of Teacher Training and Education Universitas Sebelas Maret Surakarta, 2026)
Internship program (PKL) is a learning for students to gain structured and relevant work experience before graduating from an academic program. This study aims to analyze the effect of the implementation of the Merdeka Curriculum and Field Work Practice (PKL) on the competency mastery of students in the Light Vehicle Engineering (LVE) specialization at vocational high schools (SMKs) in Kotamobagu City. The implementation of the Merdeka Curriculum is expected to improve the quality of learning through a flexible, student-centered approach, while Field Work Practice provides students with authentic workplace experience to strengthen competencies aligned with the needs of industry and the labor market. This study employed a quantitative approach with an explanatory research design. The population consisted of Light Vehicle Engineering students from four vocational high schools in Kotamobagu City who had completed their Field Work Practice program. Data were collected using questionnaires and analyzed using multiple linear regression to determine the partial and simultaneous effects of the independent variables on students' competency mastery. The findings are expected to indicate that both the implementation of the Merdeka Curriculum and Field Work Practice have a positive and significant effect on students' competency mastery. Simultaneously, these two variables contribute to improving students' knowledge, technical skills, and professional attitudes in accordance with industry requirements. The results of this study are expected to provide valuable insights for schools, teachers, and industry partners in optimizing the implementation of the Merdeka Curriculum and Field Work Practice programs to produce competent, professional, and work-ready vocational graduates